Comparative analysis of carbon dots from bamboo, coconut and mahogany wood for copper (II) ion sensing - Muega, Sherwin C.; De Luna, Mark Daniel G.; Paoprasert, Peerasak (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
The management of large amount of wood waste generated from various industries remains a very challenging issue. However, wood waste is an inherently renewable resource that can be recycled and utilized for the production of green products and renewable energy. In this work, carbon dots (CDs) was successfully synthesized using wood wastes, specifically bamboo, coconut and mahogany wood as the carbon sources via pyrolysis-hydrothermal method. BCDs, CCDs and MCDs obtained relative quantum yields of 2.68, 1.76 and 2.02% and have diameters ranging from 4 - 8 nm. BCDs, CCDs and MCDs were also examined using transmission electron microscopic (TEM), x-ray photoemission spectroscopic (XPS), Fourier transform infrared (FT-IR), UV-Vis and fluorescence spectroscopic studies to obtain their structural characteristics and optical properties. Moreover, BCDs, CCDs and MCDs were used to detect metal ions and found out to be selective in copper (II) ion, with a limit of detection of 48.83 uM, 10.27 uM and 55.46 uM respectively. In addition, paper-based sensor was prepared using CCDs for a practical application of Cu2+ sensing. The paper-based sensor exhibit decreased fluorescence illumination under UV light in the presence of Cu2+ compared to other metal ions. Furthermore, the effects of different Cu2+ concentrations in the fluorescence illumination of CCD paper-based strips were investigated. The results show that wood wastes can be utilized by producing carbon quantum dots which can be used in various sensing and environmental applications due to its properties.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Wood waste -- Recycling; Carbon dots